Discovery and preliminary structure–activity relationship studies on tecomaquinone I and tectol as novel farnesyltransferase and plasmodial inhibitors. Issue 14 (15th July 2016) - Cadelis, Melissa M.; Bourguet-Kondracki, Marie-Lise; Dubois, Joëlle; Valentin, Alexis; Barker, David; Copp, Brent R.
Graphical abstract: Abstract: Biological screening of a library of synthesized benzo[ c ]chromene-7, 10-dione natural products against human farnesyltransferase (FTase) has identified tecomaquinone I (IC50 of 0.065 ± 0.004 μM) as being one of the more potent natural product inhibitors identified to date. Anti-plasmodial screening of the same library against a drug-resistant strain of Plasmodium falciparum identified the structurally-related dichromenol tectol as a moderately active growth inhibitor with an IC50 3.44 ± 0.20 μM. Two novel series of analogues, based on the benzo[ c ]chromene-7, 10-dione scaffold, were subsequently synthesized, with one analogue exhibiting farnesyltransferase inhibitory activity in the low micromolar range. A preliminary structure–activity relationship (SAR) study has identified different structural requirements for anti-malarial activity in comparison to FTase activities for these classes of natural products. Our results identify tecomaquinone I as a novel scaffold from which more potent inhibitors of human and parasitic FTase could be developed.